Inovasi Sistem Pembelajaran Matematika pada Masa Pandemi Covid 19 di MTs Al-Fajar Kandat Kediri - Mahda Sofiyana Khoirun Nisa; Agustinayanti; Muhammad Asrori Ma’sum (Abdimas Indonesian Journal, 2022)
The purpose of this study was to determine the learning system used in mathematics subjects at MTs Al – Fajar Kandat and to obtain related information experienced by students in learning mathematics during the covid-19 pandemic. The COVID-19 pandemic has had an impact on the progress of the education sector. Therefore, teachers and schools can choose learning media that are easy to reach by students. The method used in this research is qualitative. The data was obtained from the results of an interview with a 9C grade student at MTs Al – Fajar. The results of this study are the learning system for mathematics subjects at MTs Al - Fajar Kandat using two systems, the first is a daring learning system, in which the teacher provides material by sending a You Tube link and sending assignments to the Whats App Group. Then to collect assignments via private chat to the math teacher via Whats App. Constraints experienced by students in bold learning are the lack of understanding of the material presented and students are still confused with the material. The second learning system is the offline learning system, in this system it is only carried out when there is a Mid-Semester Examination and a Final Semester Examination. In this system students carry out face-to-face exam activities using the question sheet provided by the teacher. Due to a lack of understanding when learning to be brave, the impact experienced by students in learning to be brave is that the student's grades go down.